Is social responsibility a normal good? - Björn Bartling; Vanessa Valero; Roberto A. Weber (University of Zurich, Department of Economics, 2018)
We investigate whether growth in consumer income causes an increased willingness to pay to mitigate negative externalities from consumption. Correlational field evidence suggests a positive relationship between income and social responsibility. To investigate a causal link, we conduct a laboratory market experiment in which firms and consumers can exchange products that differ in the degree to which they mitigate negative external impacts at the expense of higher production costs. Our treatments exogenously vary consumers' incomes. Our experimental results reveal that growth in consumer income causes an increase in the share of socially responsible consumption in the laboratory. Such a causal relationship is significant from a policy perspective, as it implies that some negative external impacts of consumption activity can be mitigated as societies experience economic growth.
Keywords: C92; D31; D62; M14; 330; Social responsibility; income growth; normal goods; laboratory experiment; market game